Building blocks to the future of regenerative medicine: organoid bioprinting - Tan, Nathanael (2022)
Despite being valuable models of study, organoids can be limited in their usefulness due to their small millimeter scale. In a letter in Nature Materials, Lutolf and his team at the Ecole Polytechnique Fédérale de Lausanne (EPFL) designed an innovative three-dimensional (3D) bioprinting concept that they termed bioprinting-assisted tissue emergence (BATE), overcoming organoids limits by using them as building blocks to mimic macroscale in vivo tissue. Their novel approach, combining the precision of bioprinting with the self-organizing potential of organoids, opens the path for new breakthroughs in regenerative medicine because of the potential of the engineered tissue to mimic native organ boundaries as well as tissue-tissue interactions.